On the dynamics of quark-quark interaction - Desimirov, Georgi (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
For heavy quarkonia, a model with effective propagators (with a gluon covariant propagator) is applied. Bound state is described in the framework of Longunov-Tavkhelidze quasipotential approach. An one-gluon-exchange diagram is taken into account and the usual coupling constant is used. The $s$-states of heavy quarkonia are considered. The description of experimental data by quark models appears promising.